Anticancer Activities of Flavonoids: Mechanisms of Actions - Suttana, Wipob (Srinagarind Medical Journal, 2013)
Flavonoids are natural compounds which exhibit anticancer activities including antiproliferation, cell cycle arrest and apoptosis induction. Furthermore, flavonoids can inhibit cancer-related inflammation, angiogenesis, metastasis and multidrug resistance. The molecular mechanisms of these actions are associated with the blockage of cell signaling transduction and NFkB-dependent gene expression. The mitochondrial damage affecting cellular energetic state also plays an important role in the anticancer mechanisms of flavonoids. In addition to direct actions on cancer cells, flavonoids can suppress immune response and VEGF release of vascular smooth muscle cells resulting in the inhibition of cancer-related inflammation and angiogenesis, respectively. Therefore, flavonoids are potential compounds for cancer treatment through apoptotic induction, inhibition of cancer progress and overcoming multidrug resistance. This information is important for the development of anticancer drug derived from flavonoids.